2016
DOI: 10.1136/annrheumdis-2016-eular.1213
|View full text |Cite
|
Sign up to set email alerts
|

AB0508 Serum and Urinary Interferon-Gamma-Inducible Protein 10 in Lupus Nephritis

Abstract: BackgroundLupus nephritis (LN) is one of the serious complications of systemic lupus erythematosus (SLE). Finding reliable non-invasive biomarkers for LN will help to improve disease outcomes. IFN-γ-inducible protein 10 (IP-10) is a pro-inflammatory chemokines which is involved in the immunopathogenesis of LN. Thus, we investigated the role of IP-10 as a potential marker of LN.ObjectivesTo identify the sensitivity, specificity and cut-off value of serum and urinary IP-10 level in LN patients compared to albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Defining improved noninvasive diagnostics and novel therapeutic targets for lupus nephritis (LN) will facilitate better disease management, and studies have implicated interferon (IFN)-γ-induced protein 10 (IP-10) as a candidate serum and urine marker for autoimmune activity and LN in SLE patients [ 9 , 10 , 11 , 12 , 13 ]. A meta-analysis published in 2019 thoroughly analyzed and reviewed data from 15 reports presenting serum and/or urine IP-10 protein levels in the context of disease activity in SLE patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining improved noninvasive diagnostics and novel therapeutic targets for lupus nephritis (LN) will facilitate better disease management, and studies have implicated interferon (IFN)-γ-induced protein 10 (IP-10) as a candidate serum and urine marker for autoimmune activity and LN in SLE patients [ 9 , 10 , 11 , 12 , 13 ]. A meta-analysis published in 2019 thoroughly analyzed and reviewed data from 15 reports presenting serum and/or urine IP-10 protein levels in the context of disease activity in SLE patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…T cells, neutrophils, monocytes, and endothelial cells secrete IP-10, and enhanced serum levels are reported in a number of systemic autoimmune diseases, including rheumatoid arthritis, systemic sclerosis, and SLE [ 7 , 8 ]. A role for IP-10 in LN is implicated from several reports showing enhanced IP-10 mRNA or protein levels in serum, urine, kidney biopsies, or circulating immune cells in patients with SLE with active LN [ 9 , 10 , 11 , 12 , 13 ]. A recent meta-analysis of studies investigating IP-10 as a potential biomarker for SLE/LN concluded that urinary, but not serum levels of IP-10 were significantly elevated in patients with active-LN versus active-SLE/without LN [ 14 ].…”
Section: Introductionmentioning
confidence: 99%